FEM Simulation of FDS Response in Oil-Impregnated Paper Insulation of Current Transformers with Axial Aging Variation - Lujia Wang; Yutong Zhang; Ling Yang; Xiaoyu Hu; Sien Xu; Weimin Huang; Longzhen Wang (Energies, 2025)
The aging of oil-impregnated paper (OIP) insulation is one of the key factors influencing the service life of oil-immersed current transformers. Frequency domain spectroscopy (FDS), supported by mathematical models or simulation methods, is commonly used to evaluate insulation conditions. However, traditional aging models typically ignored significant aging differences between the transformer OIP head and straight sections caused by the axial temperature gradient. To address this limitation, an accelerated thermal aging experiment was performed on a full-scale oil-immersed inverted current transformer prototype. Based on the analysis of its internal temperature field, the axial temperature gradient boundary of the main insulation was identified. By applying region-specific aging control strategies to different axial segments, a FEM model incorporating axial aging variation was developed to analyze its influence on FDS. The simulation results closely matched experimental data, with a maximum deviation below 9.22%. The model’s applicability was further confirmed through the aging prediction of an in-service transformer. The proposed model is expected to provide a more accurate basis for predicting the FDS characteristics of OIP insulation in current transformers.